Exploring The Role of Emotional Triggers and Advertising Authenticity on Purchase Intention Through Short Video Marketing in Indonesia - Styaningrum, Etik Dwi; Suleman, Dede; Haryati, Raden Ati; Wianti, Wiwin; Sofyanty, Devy (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study aims to explore how advertising authenticity and emotional triggers influence consumer purchase intention through emotional engagement in the context of short-form video advertising in Indonesia. To achieve this objective, this study uses a quantitative approach with a survey design. Respondents consisted of active TikTok and Instagram Reels users in Indonesia who, in the past three months, have watched or interacted with short-form video advertisements. Data collection was conducted online using a structured questionnaire, then analyzed using the Structural Equation Modeling (SEM) technique. The results showed that advertising authenticity and message relevance significantly increased emotional arousal and nostalgia. Both affective responses were shown to drive emotional engagement, leading to increased purchase intentions. Emotional arousal was identified as the strongest predictor of engagement and impulsive decisions. This study extends the Cognitive–Affective–Conative (CAC) model to short video marketing and highlights nostalgia as a culturally relevant emotion in Indonesia. Despite these findings, the study's cross-sectional design limits causal interpretation; future studies should adopt longitudinal approaches. Brands are advised to focus on authentic storytelling and emotionally charged narratives within brief short video formats.